Mammary Stem Cells: Premise, Properties, and Perspectives. Issue 8 (August 2017) - Lloyd-Lewis, Bethan; Harris, Olivia B.; Watson, Christine J.; Davis, Felicity M.
Abstract : Adult mammary stem cells (MaSCs) drive postnatal organogenesis and remodeling in the mammary gland, and their longevity and potential have important implications for breast cancer. However, despite intense investigation the identity, location, and differentiation potential of MaSCs remain subject to deliberation. The application of genetic lineage-tracing models, combined with quantitative 3D imaging and biophysical methods, has provided new insights into the mammary epithelial hierarchy that challenge classical definitions of MaSC potency and behaviors. We review here recent advances – discussing fundamental unresolved properties of MaSC potency, dynamics, and plasticity – and point to evolving technologies that promise to shed new light on this intractable debate. Elucidation of the physiological mammary differentiation hierarchy is paramount to understanding the complex heterogeneous breast cancer landscape. Trends: The ability of stem cells to generate and repeatedly regenerate the elaborate mammary epithelium at any stage during the female reproductive lifespan reveals the extraordinary capacity and longevity of stem cells in the adult mammary gland (breast). Some breast cancers may also be hierarchically organized, containing cancer stem cells that propel and sustain tumor growth and therapy-resistant regrowth. The adoption and refinement of novel mouse models, imaging techniques, and quantitative methodologies have provided insights into the mammary epithelial cell hierarchy that could not have been achieved using conventional approaches. Evolving techniques to label, trace, and profile individual cells, both in the normal mammary gland and in tumors, will offer further insights into the capacity, multiplicity, and dynamicity of mammary stem cells and their malignant counterparts.